2019
DOI: 10.2147/ott.s227156
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circulating Cell-Free DNA or Circulating Tumor DNA in the Management of Ovarian and Endometrial Cancer</p>

Abstract: Ovarian cancer (OC) is the most lethal cancer of all gynecological malignancies, while endometrial cancer (EC) is the most common one. Current strategies for OC/EC diagnosis consist of the extraction of a solid tissue from the affected area. This sample enables the study of specific biomarkers and the genetic nature of the tumor. However, the tissue extraction is risky and painful for the patient and in some cases is unavailable in inaccessible tumors. Moreover, a tissue biopsy is expensive and requires a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 120 publications
0
34
0
Order By: Relevance
“…Endometrial cancer is the most common malignant cancer of women's reproductive tract [117]. It can be diagnosed and treated in early stages due to typical symptoms [125]. Histopathology examination is a gold standard in the diagnosis of endometrial cancer, but due to its invasive nature, it cannot serve as a clinical monitoring method [125].…”
Section: Claudins In Endometrial Cancermentioning
confidence: 99%
“…Endometrial cancer is the most common malignant cancer of women's reproductive tract [117]. It can be diagnosed and treated in early stages due to typical symptoms [125]. Histopathology examination is a gold standard in the diagnosis of endometrial cancer, but due to its invasive nature, it cannot serve as a clinical monitoring method [125].…”
Section: Claudins In Endometrial Cancermentioning
confidence: 99%
“…Furthermore, genetic testing of cell-free DNA (e.g., fetal and tumor) allows for early detection of disease, tracking recurrence in cancers, and even non-invasive prenatal genetic testing where mutations of the fetus are detected in a pregnant mother's blood [8,9]. Recent studies have demonstrated that screening for mutations in circulating tumor or cell-free DNA can allow for the early detection of recurring cancers [10][11][12][13][14][15][16][17]. Therefore, rapid and precise assessment of patient or cancer-specific mutational AAFs could provide important clinical benefits for families [10,11,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, ctDNA proportion in total cell-free DNA varies due to the clinical-pathologic features of tumor and tumor microenvironment. Nevertheless, the level of ctDNA in standard blood is relatively low [ 105 ] as can be illustrated by plasma that constitutes <0.01–10% of total circulating cell-free DNA [ 103 ].…”
Section: Blood Samples As Currently Most Frequently Used Liquid Bimentioning
confidence: 99%